Lymphatic vessel mapping in the upper extremities of a healthy Korean population - Yun-Whan Lee; Soo-Hyun Lee; Hi-Jin You; Jae-A Jung; Eul-Sik Yoon; Deok-Woo Kim (Archives of Plastic Surgery, 2018)
Background Intraoperative indocyanine green (ICG) lymphography can effectively detect functioning lymph vessels in edematous limbs. However, it is sometimes difficult to clearly identify their course in later-stage edematous limbs. For this reason, many surgeons rely on experience when they decide where to make the skin incision to locate the lymphatic vessels. The purpose of this study was to elucidate lymphatic vessel flow patterns in healthy upper extremities in a Korean population and to use these findings as a reference for lymphedema treatment. Methods ICG fluorescence lymphography was performed by injecting 1 mL of ICG into the second web space of the hand. After 4 hours, fluorescence images of lymphatic vessels were obtained with a near-infrared camera, and the lymphatic vessels were marked. Three landmarks were designated: the radial styloid process, the mid-portion of the cubital fossa, and the lower border of the deltopectoral groove. A straight line connecting the points was drawn, and the distance between the connected lines and the marked lymphatic vessels was measured at 8 points. Results There were 30 healthy upper extremities (15 right and 15 left). The average course of the main lymph vessels passed 26.0±11.6 mm dorsal to the styloid process, 5.7±40.7 mm medial to the mid-cubital fossa, and 31.3±26.1 mm medial to the three-quarters point of the upper landmark line. Conclusions The main functioning lymphatic vessel follows the course of the cephalic vein at the forearm level, crosses the mid-cubital point, and travels medially toward the mid-axilla.